2006
DOI: 10.1007/bf03022834
|View full text |Cite
|
Sign up to set email alerts
|

Les effets des anesthésiques volatils sur les complications ischémiques et la mortalité cardiaques pendant le PAC: une méta-analyse

Abstract: This meta-analysis demonstrates sevoflurane and desflurane reduce the postoperative rise in cTnI. Sevoflurane-mediated reduction in cardiac troponin was associated with improved long-term outcomes in one study. This meta-analysis was not able to show that these positive effects on troponin were translated into improved clinical outcomes. Well-designed large randomized control trials are needed to further elucidate the differential cardio-protective effects of volatile anesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(79 citation statements)
references
References 45 publications
4
68
0
7
Order By: Relevance
“…The effects of Anesthetics as cardioprotective agents are well-known and anaesthesic preconditioning (APC) is capable of a reduction of infarct size and mortality after myocardial infarction 2,3 , troponin I release after coronary artery bypass graft surgery 4 and prevention of acute kidney injury 5 . However, little is known on how APC influences the autonomic modulation of the heart after the acute phase of a myocardial ischemia-reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Anesthetics as cardioprotective agents are well-known and anaesthesic preconditioning (APC) is capable of a reduction of infarct size and mortality after myocardial infarction 2,3 , troponin I release after coronary artery bypass graft surgery 4 and prevention of acute kidney injury 5 . However, little is known on how APC influences the autonomic modulation of the heart after the acute phase of a myocardial ischemia-reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…17 Several meta-analyses showed that volatile anesthetics were associated with a reduction in postoperative troponin release, although not all showed an effect on clinical outcome. 15,18 It is possible that volatile anesthetics have a different cardioprotective effect in patients not undergoing heart surgery. 19 Therefore, to explore a potential cardioprotective effect of sevoflurane during pPCI, we performed the Sevoflurane In Acute Myocardial Infarction (SIAMI) trial.…”
Section: Résumémentioning
confidence: 99%
“…[3][4][5] In the current issue of the Journal, Ansley et al have pursued a different approach: They report the results of their clinical Phase 2 trial (PRO-TECT II) that assessed the impact of administering a targeted dose of systemic propofol during the ischemia-reperfusion interval in patients undergoing heart surgery. 6 They hypothesized that the antioxidant properties of propofol impart anesthetic preconditioning and protect ischemic myocardium from oxidative injury during cardiac surgery.…”
mentioning
confidence: 99%
“…In juxtaposition to Ansley et al, several meta-analyses have demonstrated trends toward more favorable outcomes with inhalation anesthetics. [3][4][5] Yu and Beattie assessed a heterogeneous group of studies that demonstrated a trend toward decreased mortality with inhalation anesthetics. 3 Sevoflurane and desflurane, but not isoflurane, were associated with a decrease in postoperative troponin levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation